PENGARUH KUALITAS PELAYANAN DAN DUKUNGAN SOSIAL TERHADAP PENINGKATAN PRODUKTIVITAS PEGAWAI PADA DINAS PERPUSTAKAAN DAN KEARSIPAN KOTA CILEGON - Rizal, Rizmi Samsul; Andriyani, Devi (STAI La Tansa Mashiro, 2025)
This study aims to determine the effect of service quality and social support on theimprovement of employee productivity at the Library and Archives Office of Cilegon City.The research method used is a descriptive quantitative approach with a census (saturated sampling) method, in which the entire population of 52 employees was used as respondents. Data were collected through questionnaires developed based on indicators of each research variable. The data obtained were analyzed using classical assumption tests, multiple correlation analysis, coefficient of determination (R²), and multiple linear regression analysis to determine the extent to which service quality and social support influence the improvement of employee productivity at the Library and Archives Office of Cilegon City. The results of this study are expected to provide an empirical overview of the factors that affect employee productivity and serve as a consideration for the Library and Archives Office of Cilegon City in improving work effectiveness and service quality to the community.